Soil microbial biomass and organic matter dynamics in metal-contaminated soils - Barajas-Aceves, Martha (1994)
A main aim of this thesis was to compare and evaluate different microbiological methods (total biomass or microbial activity) to detect effects of heavy metals on the functioning of the soil ecosystem. The biomass methods, which included biomass C, biomass ninhydrin-N, biomass N, ATP, substrate induced respiration and the activity methods, which included CO, evolution and arginine ammonification reliably detected effects of heavy metals on the soil microbial ecosystem in metal-contaminated soils from the Woburn Market Garden Experiment which contained, due to past sludge applications, Zn, Cu or Ni at around current European Union (EU) upper limits and Cd at around three times the limit. Most microbiological indices were decreased by up to about 50% in the most metal- contaminated soils and the results were comparatively simple to interpret.